The relationship between alcohol problems, perceived risks and attitudes toward alcohol policy in Canada - Macdonald, S.; Stockwell, Tim; Luo, J. (2011)
Introduction and Aims: Approval of alcohol policies by the public in democratic countries is critical for instituting social change. With respect to alcohol policies, mounting research indicates that a higher price per unit of ethanol is an effective approach for reducing alcohol-related problems, yet surveys have found this approach is usually unpopular. The purpose of this paper is to assess the relationship between amount of drinking and support for various alcohol policies. Design and Methods: A secondary analysis was conducted on the Canadian Addictions Survey, a randomised telephone survey of over 10000 Canadians. The relationship between the amounts of drinking reported by the respondents was examined in relation to the perceived seriousness of alcohol problems in their communities and the endorsement of several alcohol policies. Results: Increased amount of drinking was significantly related to lower perceptions of drinking-related risks. Furthermore, heavier consumers had less favourable attitudes than lighter drinkers and abstainers toward alcohol policies, such as increased taxation. Aggregated data across the 10 Canadian provinces showed a strong effect size (r=-0.515, P=0.128) between endorsement of alcohol taxation and rates of hospital separations for alcohol. Discussion and Conclusions: Results from this study show that the more that people drink, the more they oppose taxation. The implications of these findings are that as alcohol problems in communities become worse, the population may become more resistant to effective alcohol policies. Strategies are suggested for implementing effective policies.